Zhodnocení metod pro stanovení tenzidů - Soukupová, Alena (Vysoké učení technické v Brně. Fakulta chemická, 2009)
V bakalářské práci na téma zhodnocení metod pro stanovení tenzidů byl na základě dostupné literatury vypracován seznam možných metod používaných pro stanovení tenzidů v povrchových a odpadních vodách. V teoretické části jsou uvedeny definice povrchové a odpadní vody, možné zdroje znečištění a způsoby čištění a dále definice a dělení tenzidů. Práce je teoretického charakteru a zpracování bylo provedeno na základě dostupných informací z literárních zdrojů. V závěru je provedeno zhodnocení metod.

This bachelor thesis deals with the evaluation of the methods used for the determination of surfactants. On the base of literature search the review of possible methods applicable for the determination of detergents in the surface waters and wastewaters was set up. The theoretical part presents the definitions of the surface water and wastewater, possible sources of pollution are discussed and methods of water cleaning are listed. The definition and classification of various classes of surfactants is also included. This work is theoretical; therefore the evaluation was made on the basis of the information obtained from accessible literature. The evaluation of the discussed methods is given in the conclusion.
Evaluation of methods for determination of surfactants
Keywords: tenzidy; metody stanovení; odpadní voda; povrchová voda; surfactants; methods of determination; sewage water; surfare water